Protein profiles and antimicrobial activity of common Sunda Toad, Duttaphrynus melanostictus paratoid secretions - Ahmad Zahari, Muhammad Syafiq; Darnis, Deny Susanti; Tengku Abdul Hamid, Tengku Haziyamin (International Institute of Chemical, Biological & Environmental Engineering (IICBEE), 2015)
In this study, the profile and antimicrobial activity of the secretions of Duttaphrynus melanostictus were studied. The protein profiles were investigated through SDS-PAGE and the proteins itself has been successfully separated. The antimicrobial activity of the secretions was performed by disk diffusion method and was tested against Bacillus cereus ATCC11778, Escherichia coli ATCC 25922, Salmonella typhimurium IMR S 974/05 B, Staphylococcus aureus ATCC 25923, Staphylococcus eperdimidis IMR S 384/05 C, Klebsiella pneumoniae ATCC 700603 and Methicillin-resistant Staphylococcus aureus (MRSA) which had been clinically isolated. According to the findings, the secretions (5mg/ml) have lower antimicrobial activity in comparison to antibiotics used, Tetracycline HCl (120 mg/ml). The secretions however, failed to inhibit the growth of Methicillin-resistant Staphylococcus aureus.